As tramas da realidade: considerações sobre o corpo em Michel Serres - Monteiro, Ana Claudia Lima (2009)
The goal of this text is to reflect on the possibility of relating the body to the works of the contemporary French philosopher Michel Serres. This assignment proposes the body within new perspectives about itself. Therefore three possibilities of thought will be used starting with their connections: the body-texture, the body-potency and the body-narrative. It s not the intention of this paper to be linear nor excludente, due to the fact that, we believe there are merely three choices of reflection and not the complete nor entire forms of thinking of the body. Nevertheless, based on the works of Serres, we consider these connections pertinent, seeing that the author discusses these new choices in many of his books. The emphasis is mainly on five specific ones: Les Cinq Sens, Variations sur le Corps and three others of a quadrilogy on humanity: Hominescence, L Incandescent and Rameaux. The reflections presented are inside a contemporary context, in which the frontiers between what is human and what is not, are more and more tenuous as well as crossed likewise movable each moment. Thinking about the body, in this perspective, brings us to new possibilities not only about reflections but actions, because our proposal, far from being a theoretical imposition, is a practical stimulation. It forces us not to ponder about the body, but to effectively have one